Association of socio-demographic and obstetric factors with obstetric fistula patients’ perceptions towards life fulfillment in Kitovu Hospital, Uganda - Atuhaire, Shallon; Odukogbe, Akin-Tunde A.; Mugisha, John F.; Ojengbede, Oladosu A. (International Journal Of Community Medicine And Public Health, 2020)
Background: To date, obstetric fistula is one of the major public health challenges among the poorest, young women and girls in rural communities in low and middle-income countries. There is scarce information on the association of socio-demographic and obstetric factors with the obstetric fistula patients’ perceptions towards life fulfillment which compelled this study. Methods: A cross-sectional survey using a semi-structured questionnaire was done among 390 obstetric fistula patients registered within the past two years to the time of data collection at Kitovu Hospital, Masaka, Uganda. Pearson’s Chi square correlation was used to determine the association of socio-demographic and obstetric factors with perceptions towards life fulfillment using SPSS 25.0. Results: A larger proportion of obstetric fistula patients 226 (57.9%) had negative perceptions while 164 (42.1%) had positive perceptions. Maternal age, repair status, outcome of repair, self-perceived level of incontinence, and number of living children were statistically associated with patients’ perceptions towards life fulfillment at a P-value less than 0.001, marital status, p value of 0.005, and overall duration lived with fistula, p value of 0.009. A greater number of patients with tertiary education, 5 (83.3%) had positive perception, however, the association was not significant with a p value of 0.059. Fistula type, region of residence, and number of repairs were not statistically significant. Conclusions: Thus, socio-demographic and obstetric factors influence patients’ perceptions towards life a great deal. Efforts should focus on fistula prevention and timely repair so as to minimize probable experiences likely to result in negative perception that would eventually impede life fulfillment.